The effect of foam rollers of varying densities on range of motion recovery. (April 2021) - Yanaoka, Takuma; Yoshimura, Akane; Iwata, Risa; Fukuchi, Momoko; Hirose, Norikazu
Abstract: Objective: This study aimed to compare the effect of different density foam rollers on range of motion recovery. Method: Ten active men completed two, 3-day trials in random order. During the experimental trials, all participants performed 2 min of foam rolling (FR) using a medium-density (medium trial) or hard-density (hard trial) foam roller on the right posterior thigh after completing the 90-min Loughborough Intermittent Shuttle Test (LIST). The hip joint range of motion (ROM), muscle hardness, and muscle soreness were assessed before and after the LIST and at 0 min, 20 min, 60 min, 24 h, and 48 h after FR intervention. Serum creatine kinase (CK) concentrations were assessed before the LIST and at 60 min, 24 h, and 48 h after FR intervention. The contralateral leg in each trial was used as a control. Results: The ROM at 0 min, 20 min, 60 min, 24 h, and 48 h after FR intervention were higher in the right leg (the massage leg) than in the left leg (the contralateral leg) (p < 0.05). In the right leg, the ROM at 0 min after FR intervention was higher than after the LIST (p < 0.05). There were no significant differences between the medium and hard trials for ROM. Muscle hardness, muscle soreness, and serum CK concentration were not affected by FR. Conclusion: FR has a positive effect on ROM recovery. Moreover, the two roller densities provided similar ROM recovery.